Factors associated with knowledge, attitude and practices regarding HIV/AIDS infection among primary school teachers in Bichi local government of Kano State, Nigeria - Mustapha, Abdu; Ismail, Suriani; Md Said, Salmiah; Ibrahim, Faisal; Syed Hassan, Syed Tajuddin; Yakasai, Musa Garba (Community Health Society Malaysia, 2017)
Background: Even though, there is high awareness about HIV/AIDS infection among the teachers in Nigeria, studies have shown that HIV/AIDS knowledge, attitude and practices among teachers in Nigeria are very low. The main aim of this study is to determine factors associated with knowledge, attitude and practices regarding HIV/AIDS infection among primary school teachers in Bichi local government of Kano State, Nigeria. Materials and Methods: A total of 600 respondents were selected through a multi-stage random sample procedure from 13 primary schools within Bichi local government area of Kano State, Nigeria. Data was collected using validated structured questionnaire. Data was analysed using SPSS version 22.0. Chi-square test was used to test for association; level of significance was set at P < 0.05. Result: The study revealed that majority of the respondents are Male 350 (58.3%), Hausa 540 (90%), Islam 548 (91.3%), Age group 36 – 50: 333 (55.5%), Married 486 (81.0%) and National Certificate in Education (NCE) 491 (81.8%) as the minimal teaching qualification in Nigerian primary schools. There were no significant association shown between the Sociodemographic factors and knowledge, attitude and practices regarding HIV/AIDS. Conclusion: In this study, HIV/AIDS knowledge of the respondents was low, the attitude towards HIV/AIDS issues was found to be negative and the practices was poor. However, there is no association between Sociodemographic factors and HIV/AIDS knowledge, attitude and practices among the respondents.